Evaluasi Kebijakan Bantuan Pendidikan (Program Indonesia Pintar/ Bantuan Operasional Sekolah) dalam Mengatasi Anak Tidak Sekolah (ATS) dan Peningkatan Angka Partisipasi Kasat/ Angka Partisipasi Murni (APK/ APM) di Indonesia - Ivan, Muhammad (Jurnal Transformasi Administrasi, 2024)
The success of investing in education assistance through Program Indonesia Pintar (PIP) and Bantuan Operasional Sekolah (BOS) is not enough just to use a single parameter, namely only measuring the amount of funds that have been channeled, but on the accuracy of the use of funds and also the discretionary efforts made by schools to carry out supervision so that aid funds are not diverted or misused. Very wrong investment, if the aid program reaches hundreds of trillions of rupiah, but there is no evaluation at all to measure the extent of the assistance program's performance and impact. Increase in Gross Participation Rate/Net Enrollment Rate (APK/APM) and efforts to reduce the number of children dropouts (ATS) are the outcome of the success or failure of the PIP and BOS programs so far. Historically, since the implementation of PIP in 2014 and BOS in 2005 there has not been a comprehensive evaluation of the two aid programs to date. The results showed that the implementation of PIP and BOS was not significantly able to increase APK/APM and reduce the number of ATS.